For debate: health service support planning for large-scale defensive land operations (part 1). Issue 3 (19th June 2019) - Bricknell, Martin; Finn, A; Palmer, J
Abstract : This is the first of two articles that considers the medical planning implications of large-scale defensive military operations. This paper considers the military context and planning factors that may require a medical plan that is different from that seen in recent counterinsurgency operations. The scale and complexity of the challenge is likely to require a greater level of decentralisation and a more sophisticated approach to medical planning at the strategic and operational levels.